Additional file 8 of Comparative study of excretory–secretory proteins released by Schistosoma mansoni-resistant, susceptible and naïve Biomphalaria glabrata - Conor E. Fogarty; Min Zhao; Donald P. McManus; Mary G. Duke; Scott F. Cummins; Tianfang Wang (figshare, 2022)
Additional file 8: Table S5. A list of the total proteins, unique proteins and corresponding peptides identified in susceptible B. glabrata SCW with reference to the S. mansoni proteome, and enriched GO terms related to the proteins.
Keywords: Biochemistry; Medicine; Microbiology; Environmental Sciences not elsewhere classified; Ecology; Immunology; Biological Sciences not elsewhere classified; Cancer; Science Policy; Virology